2015
DOI: 10.1055/s-0035-1564793
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound: Current Status for Image-Guided Therapy

Abstract: Image-guided high-intensity focused ultrasound (HIFU) is an innovative therapeutic technology, permitting extracorporeal or endocavitary delivery of targeted thermal ablation while minimizing injury to the surrounding structures. While ultrasound-guided HIFU was the original image-guided system, MR-guided HIFU has many inherent advantages, including superior depiction of anatomic detail and superb real-time thermometry during thermoablation sessions, and it has recently demonstrated promising results in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 127 publications
(158 reference statements)
0
77
0
1
Order By: Relevance
“…Applications of MR‐guided focused ultrasound (MRgFUS) with CE mark and US FDA approval include ablation of uterine fibroids and bone metastases‐related pain management, while the clinical use of MRgFUS for the treatment of breast cancer is still waiting for CE and US FDA approval. However, several clinical studies and reviews showed the potential role of this technique for breast benign and malignant lesions ablation . The most commonly used devices are the ExAblate systems 2000 and 2001 (Fig.…”
Section: Hifu Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of MR‐guided focused ultrasound (MRgFUS) with CE mark and US FDA approval include ablation of uterine fibroids and bone metastases‐related pain management, while the clinical use of MRgFUS for the treatment of breast cancer is still waiting for CE and US FDA approval. However, several clinical studies and reviews showed the potential role of this technique for breast benign and malignant lesions ablation . The most commonly used devices are the ExAblate systems 2000 and 2001 (Fig.…”
Section: Hifu Ablationmentioning
confidence: 99%
“…However, several clinical studies and reviews showed the potential role of this technique for breast benign and malignant lesions ablation. 44,51,[54][55][56][57][58] The most commonly used devices are the ExAblate systems 2000 and 2001 (Fig. 2, GE Healthcare, and InSightec-TxSonics, Israel) and the Sonalleve MR HIFU system (Philips, Best, The Netherlands).…”
Section: Hifu Ablationmentioning
confidence: 99%
“…Ultrasound imaging-guided HIFU treatment has been widely performed because it is real-time and cost-effective. 22 However, there are several issues in this approach which require more exploration, including the hyperechoic changes on both the treated target and surrounding tissue during heating, relatively low tissue contrast, and a limited field of view. 22 Many studies have also reported thermal monitoring of cancer treatment using magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…22 However, there are several issues in this approach which require more exploration, including the hyperechoic changes on both the treated target and surrounding tissue during heating, relatively low tissue contrast, and a limited field of view. 22 Many studies have also reported thermal monitoring of cancer treatment using magnetic resonance imaging (MRI). 14,23,24 It has shown potential application in the clinic because of its superior depiction of three-dimensional (3D) anatomic structure, high tissue contrast, and real-time thermometry during thermal ablation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation